Real-world stress and control: integrating ambulatory physiological and ecological momentary assessment technologies to explain daily wellbeing - Lohani, Monika; Dutton, Samuel; Imel, Zac E.; Hill, Patrick L. (Frontiers in Psychology, 2025)
The current study sought to advance our understanding of the connections between stress, perceived control, affect, and physiology in daily life. To achieve this goal, we integrated hourly ambulatory physiological and experiential data from young adult participants who experienced work or academic stressors over the course of a day. Participants wore a cardiovascular monitor that recorded heart rate data continuously for 8 h while hourly random Ecological Momentary Assessment (EMA) data were collected in personally relevant settings via mobile phones to learn about stress, perceived control, and affect. The current findings provide a critical advance by demonstrating clear evidence for moderation by perceived control, wherein affective wellbeing was strongly associated with heart rate when one experienced a stressor outside their control. The innovative approach utilized in the current study in real-world settings provides further support for the value of integrating individuals' self-report and physiological experiences (e.g., the role of perceived control), as the information gained can provide critical insights into stress physiology (e.g., heart rate) and wellbeing (e.g., negative affect) connections. The present study thus provides a critical advance to the literature by connecting the literature on daily affect, perceived control, and physiological data streams. This innovation is particularly noteworthy given the general paucity of work that employs ambulatory assessments of physiological responses to daily life.